2020
DOI: 10.2147/dddt.s224343
|View full text |Cite
|
Sign up to set email alerts
|

<p>AZD4547 Attenuates Lipopolysaccharide-Induced Acute Kidney Injury by Inhibiting Inflammation: The Role of FGFR1 in Renal Tubular Epithelial Cells</p>

Abstract: Introduction: Inflammation plays an important role in the pathogenesis of acute kidney injury (AKI). Fibroblast growth factor receptor 1 (FGFR1) signaling is implicated in kidney pathology. AZD4547 is a small molecule inhibitor of FGFR1. Materials and Methods: Here, we investigated whether AZD4547 could mitigate inflammatory responses in AKI. C57BL/6 mice were injected with lipopolysaccharide (LPS) to induce AKI. FGFR1 was blocked using AZD4547 or CRISPR/Cas9 genome editing. After immunofluorescent double-stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition, FGFR inhibition has been found to protect against LPS-induced kidney fibrosis and dysfunction. 14 Thus, the function of FGFR1 in kidney diseases may depend on the cell types and disease types. It would be a worthwhile effort to investigate the activity of FGFR1 in other renal cells in response to Ang II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, FGFR inhibition has been found to protect against LPS-induced kidney fibrosis and dysfunction. 14 Thus, the function of FGFR1 in kidney diseases may depend on the cell types and disease types. It would be a worthwhile effort to investigate the activity of FGFR1 in other renal cells in response to Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the study showed that pharmacological FGFR inhibitor AZD4547 significantly reduced renal inflammation, cell apoptosis, and kidney dysfunction in LPS-challenged mice. 14 Second, transgenic mice with inducible cardiac-specific overexpression of a constitutively active FGFR1 develop cardiac hypertrophy and fibrosis. 15 The exciting possibility that Ang II mediates renal fibrosis in models of hypertensive kidney disease is the focus of the present study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the AKI group (n=10), LPS in 200 µl saline was administrated via intraperitoneal (i.p.) injection (10 mg/kg, 0.2 ml/mouse) for 24 h to induce AKI ( 22 ), while an equal volume of saline was given to control mice (n=10). Ethical approval was obtained from the Animal Experimentation Ethics Committee of the School of Medicine, Shanghai Jiao Tong University (approval no.…”
Section: Methodsmentioning
confidence: 99%
“…However, inhibition of FGFR1 signalling reduces EndMT in ECs. Further, Terzuoli et al 78 found that pharmacological inhibition of FGFR1 by AZD4547 blocked the formation of the FGFR1/TRAF6 complex, hence inhibiting TRAF6/NF‐κB inflammatory signalling and attenuating renal inflammatory injury and renal dysfunction. It has also been reported that diabetic FGFR1 knockout mice have significantly higher EndMT and EMT levels than diabetic control mice 79 …”
Section: Endmt and Dkdmentioning
confidence: 99%